2003
DOI: 10.1002/bit.10626
|View full text |Cite
|
Sign up to set email alerts
|

Combined transcriptome and proteome analysis of Escherichia coli during high cell density culture

Abstract: Combined transcriptome and proteome analysis was carried out to understand metabolic and physiological changes of Escherichia coli during the high cell density cultivation (HCDC). The expression of genes of TCA cycle enzymes, NADH dehydrogenase and ATPase, was up-regulated during the exponential fed-batch period and was down-regulated afterward. However, expression of most of the genes involved in glycolysis and pentose phosphate pathway was up-regulated at the stationary phase. The expression of most of amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
103
2
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(122 citation statements)
references
References 31 publications
(36 reference statements)
13
103
2
3
Order By: Relevance
“…A short-term goal of this project and the focus of this study was to assess the capability of one multiple deletion strain (E. coli MDS40) under industrial conditions. Since conditions in a fermenter, especially high cell densities, are significantly different from those in shake flasks, both of these conditions were examined (Andersson et al, 1996;Gill et al, 2001;Humphrey, 1998;Lee, 1996;Yoon et al, 2003). Under the conditions assessed E. coli MDS40 and its parent strain E. coli MG1655 had similar performance characteristics.…”
Section: Fed-batch Fermentationmentioning
confidence: 99%
“…A short-term goal of this project and the focus of this study was to assess the capability of one multiple deletion strain (E. coli MDS40) under industrial conditions. Since conditions in a fermenter, especially high cell densities, are significantly different from those in shake flasks, both of these conditions were examined (Andersson et al, 1996;Gill et al, 2001;Humphrey, 1998;Lee, 1996;Yoon et al, 2003). Under the conditions assessed E. coli MDS40 and its parent strain E. coli MG1655 had similar performance characteristics.…”
Section: Fed-batch Fermentationmentioning
confidence: 99%
“…Most of these studies have been carried out in flask cultures, whereby non defined conditions were applied [3]. In accordance with good experimental design it is important to ensure that the changes in expression profiles are due to the perturbing event.…”
Section: Resultsmentioning
confidence: 99%
“…These findings open the possibility of developing new strategies to optimize strains for the synthesis of a diversity of added-value chemicals, such as biofuels and chemical precursors. It has been reported that in high-density cultures, such as those used in industrial fermentations, there is a significant increase in the levels of several chaperones, such as DnaK and GroEL (57). While the results presented in this study constitute a proof of concept, demonstrating that expression of GroEL and PhaP can enhance solvent tolerance and bioproduct yield in small-scale cultivations, further research will be necessary to analyze the beneficial effects of these proteins in bioreactor cultures, in which cells are exposed to multiple stresses.…”
Section: Discussionmentioning
confidence: 99%